Noncollinear effective anisotropies in exchange coupled NiFe/IrMn bilayers - Mishra S.K. (My University, 2025)
The influence of noncollinearity between unidirectional and uniaxial anisotropies on asymmetric magnetization reversal of NiFe/IrMn bilayers has been investigated. The experimental findings show that a noncollinear effective anisotropies originates from the competition among the applied magnetic field, magnetic anisotropy and exchange coupling, and the presence of magnetic frustration at NiFe/IrMn interfaces. Azimuthal measurements of the exchange bias suggest that the degree of effective interfacial anisotropies, which can be quantified by the angle (γ) between the uniaxial and unidirectional anisotropies, plays a crucial role in determining magnetization reversal. For a variable thickness of antiferromagnet layers, the experimental findings suggest a non-monotonic correlation between the magnitude of γ and the degree of interfacial roughness. Numerical analysis has been performed by considering the magnetic frustration present at the ferromagnet/antiferromagnet interfaces, suggesting a good agreement with experimental findings. © 2019 Elsevier B.V.